Islamic financing towards economic growth: A study on 4 OIC countries - Hafnida, ,; Maamor, Selamah; Abdullah, Hussin (Islamic Business School, 2016)
Islamic financing is a new phenomenal and one of the fastest growing component on financial system. The aim of this study is to examine the relationship between Islamic financing and economic growth of 4 OIC countries by using panel data from 1990 to 2012.This study employed panel unit root test and two stages least square (2SLS) as a method. The empirical results show that government expenditure and net export have impact to economic growth. Islamic financing is positive and significantly correlated with economic growth in 4 OIC countries which reinforces the idea that a well-functioning banking system through of financial development will promotes economic growth. This study can be used by the government to take noted in offering more Islamic financing because it’s profitable to improve their income and later will increase economic growth.